Impact of Virtual Reality-Based Clinical Case Learning on Medical Knowledge and Clinical Engagement in Medical Education - Irum Naz, Abeer Anjum, Remsha Mustafa, Muhammad Awais Saleh, Maimoona Shabbir, Rabia Khurram, (Pakistan Journal of Medical & Health Sciences, 2023)
Background: Challenges in medical education in Pakistan are the lack of clinical exposure and the use of traditional methods of teaching. Virtual reality (VR) based clinical case learning is an innovative approach to bridge the gap between the theoretical knowledge and practical clinical experience. This study examines the effect of learning using VR on medical knowledge as well as clinical engagement of MBBS students in a five-year programme. Methods: This cross-sectional comparative study was done among n=200 MBBS students of Khawaja Muhammad Safdar Medical College Sialkot in Pakistan involved in all academic years (Years I–V). The group was split into the VR group (n=100), which spent 6 weeks using immersive VR clinical simulations, and the Traditional group (n=100), which performed paper-based case studies and instructor-led discussions on the same clinical scenarios. A standardized multiple-choice questionnaire (MCQ) was used to measure medical knowledge and clinical engagement was assessed through a validated survey instrument using a five-point Likert scale. Independent samples t-test was used to analyze continuous variables, and Chi-square test for categorical variables, with p < 0.05. Results: There was a significant difference in the mean MCQ scores for the VR group (85.3 ± 6.8) versus the Traditional group (77.1 ± 8.2; p < 0.001). Furthermore, the mean clinical engagement score was greater in the VR group (4.2 ± 0.6) than in the Traditional group (3.5 ± 0.7; p < 0.001). No significant difference (p > 0.05) was found in baseline demographic variables, age, gender, and MBBS year distribution, between the groups. Conclusion: Medical knowledge and clinical engagement of MBBS students in Pakistan are improved significantly by VR based clinical case learning. These findings indicate that the use of immersive VR technology as an adjunct to traditional teaching methods in the medical curriculum could improve clinical competence in resource constrained educational settings. Keywords: Virtual Reality, Medical Education, Clinical Engagement, MBBS, Pakistan, Simulation-Based Learning, Clinical Case Learning